Amide‐Directed C−H Sodiation by a Sodium Hydride/Iodide Composite. Issue 23 (27th April 2017) - Huang, Yinhua; Chan, Guo Hao; Chiba, Shunsuke
Abstract: A new protocol for amide‐directed ortho and lateral C−H sodiation is enabled by sodium hydride (NaH) in the presence of either sodium iodide (NaI) or lithium iodide (LiI). The transient organosodium intermediates could be transformed into functionalized aromatic compounds. Abstract : New direction : An amide‐directed ortho and lateral C−H sodiation is enabled by sodium hydride (NaH) in the presence of either sodium iodide (NaI) or lithium iodide (LiI). The transient organosodium intermediates could be transformed into functionalized aromatic compounds.